KPT-8602, a second-generation inhibitor of XPO1-mediated nuclear export, is well tolerated and highly active against AML blasts and leukemia-initiating cells - Etchin, J (Leukemia, 2017)
Acute myeloid leukemia (AML) is a clonal hematologic malignant disease of developing myeloid cells that have acquired aberrant survival, uncontrolled proliferation and a block in normal hematopoietic cell differentiation. Standard chemotherapy often induces remissions in AML patients, but the disease frequently relapses due to incomplete targeting of leukemia-initiating cells (LICs), emphasizing the need for novel effective treatments. Exportin 1 (XPO1)-mediated nuclear export, which is inhibited by the drug selinexor, is an attractive new therapeutic target in AML. Selinexor has shown impressive activity in Phase I/II clinical trials for AML. Here we report the anti-leukemic efficacy and tolerability of KPT-8602, a second-generation XPO1 inhibitor. KPT-8602 demonstrates substantially reduced brain penetration compared to selinexor, with resultant attenuation of the central nervous system mediated side effects of anorexia and weight loss. Due to its improved tolerability profile, KPT-8602 can be given daily compared to the two or three times weekly regimen of selinexor, and exhibits greater anti-leukemic efficacy against both leukemic blasts and LICs in AML patient-derived xenograft models. Importantly, normal hematopoietic stem and progenitor cell (HSPC) frequency is not significantly reduced by KPT-8602, providing a therapeutic window for elimination of relapse-driving LICs while sparing normal HSPCs. These findings strongly endorse clinical testing of KPT-8602 in patients with relapsed and refractory AML.